2005
DOI: 10.1017/s1479050505001614
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into biofilms in a local drinking water distribution system

Abstract: Biofilm growth within a water distribution system could lead to operational problems such as pipe corrosion, water quality deterioration and other undesirable impacts in water distribution systems. With the high ambient temperatures experienced in Singapore, the operating environment in water distribution systems is expected to be more conducive to biofilm development. We have recently conducted a survey on biofilms potentially present in a local water distribution system.The survey results indicated that resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Biofilms can be found nearly everywhere, such as in groundwater, pipelines in waterworks, wastewater treatment plants, on the surfaces of heat exchanger plates and biomedical devices, and on ship hulls [1][2][3][4][5]. Flow displacement systems are widely used to study bacterial adhesion to surfaces [6][7][8][9][10] as they allow control of hydrodynamic conditions, including shear rates and mass transport.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms can be found nearly everywhere, such as in groundwater, pipelines in waterworks, wastewater treatment plants, on the surfaces of heat exchanger plates and biomedical devices, and on ship hulls [1][2][3][4][5]. Flow displacement systems are widely used to study bacterial adhesion to surfaces [6][7][8][9][10] as they allow control of hydrodynamic conditions, including shear rates and mass transport.…”
Section: Introductionmentioning
confidence: 99%
“…Over 95% of the bacteria in drinking water distribution systems (DWDS) are found in biofilms (Hu et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms in DWDS can lead to problems of taste, turbidity and odour (Momba et al. 1999), pipe corrosion (Hu et al. 2005), and can also be a reservoir for human pathogens (Momba et al.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that biofilm bacteria grown on different surfaces increase resistance to different chlorine-based agents (LeChevallier et al 1988). doi: 10.2166/wh.2009.303 In a survey conducted by Hu et al (2005), a high biofilm growth potential in a drinking water distribution system was found even with the presence of residual chlorine.…”
Section: Introductionmentioning
confidence: 99%